Analisis Politik Hukum Islam Berbasis Maqoshid Syari’ah (Studi Terhadap Konsep Anak Sah Dalam Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan) - Asmuni, Asmuni; Firman, Agus (UI Scholars Hub, 2022)
This article aims to use maqashid sharia to analyze the conformity of the rules regarding legitimate children in Article 42 of the Marriage Law (UUP) with sharia principles. At the level of application of the law, it will also be seen whether the regulation is in accordance with the basic principles of maqashid. The results of this study indicate that the provisions of Article 42 UUP which equate the status of children born 'as a result of' and 'in' a legal marriage, are not in accordance with sharia principles. The Office of Religious Affairs (KUA) in determining marriage guardians for children born 'in' marriage also does not fully comply with the provisions of this article. On the basis of this fact, it is necessary to amend the formulation of Article 42 UUP so that it is in accordance with sharia principles. Furthermore, the formulation of the Article is amended by only emphasizing that a legitimate child is a child born 'as a result of' a legal marriage. Or if the old formula is to be maintained, there must be an additional article or explanation regarding the differences in the rights of children born 'as a result of' with children born 'in' a legal marriage